A model of breakup of a rising bubble in a turbulent flow. (23rd November 2020) - Eskin, D.; Meretskaya, E.; Vikhansky, A.
Highlights: A model of breakup of a bubble rising in a turbulent flow was developed. Critical Weber number for a bubble, deformed due to rising, was evaluated. Bubble dispersion in a turbulent horizontal pipe flow was simulated. Results of CFD simulations of a pipe flow were compared with experimental data. Abstract: Breakup of a bubble, rising under gravity in a turbulent flow, is analyzed. A model developed represents the critical Weber number of a bubble, indicating bubble breakup conditions, as a function of deformation caused by bubble rising. An ellipsoidal bubble shape is assumed. A simplified model of bubble deformation allows to obtain an analytical expression for the critical Weber number. An equation for the sepcific breakup rate of a rising bubble is also suggested and, then, validated against experimental data. The model developed is incorporated into the developer's version of the adaptive multiple size-group (A-MuSiG) method of the Simcenter STAR-CCM+® CFD code. A good agreement of computed data vs. experimental results is demonstrated for a bubbly flow in a horizontal pipe without tuning any adjustable parameters.